2021
DOI: 10.3390/curroncol28050312
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the Gamma Secretase Inhibitor AL101 in Desmoid Tumors: A Case Report of 2 Adult Cases

Abstract: Desmoid tumors (aggressive fibromatosis) are soft tissue mesenchymal tumors that can be locally invasive and life-threatening. Depending on the location, these tumors are often unresectable or tend to recur after surgery. To date, there are no approved systemic therapies for desmoid tumors. These tumors typically harbor mutations in the β-catenin oncogene CTNNB1 or the tumor suppressor gene adenomatous polyposis coli, resulting in constitutive activation of the WNT pathway. The Notch pathway is part of the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The maximum tolerated dose was 4 mg QW with no dose-limiting toxicities in seven evaluable patients, and 6 mg Q2W with 1 dose-limiting toxicity in six evaluable patients (grade 3 diarrhea) 98 . Long-term follow-up of one patient from the phase 1 trial and a second patient enrolled in a compassionate use program reported confirmed partial responses (41 and 60% maximal tumor reduction from baseline) observed after 1.0 and 1.6 years of treatment with AL101, with response durations of 8.6+ and 2.6+ years, respectively 83 .…”
Section: Inhibition Of γ-Secretase In Dtmentioning
confidence: 86%
See 2 more Smart Citations
“…The maximum tolerated dose was 4 mg QW with no dose-limiting toxicities in seven evaluable patients, and 6 mg Q2W with 1 dose-limiting toxicity in six evaluable patients (grade 3 diarrhea) 98 . Long-term follow-up of one patient from the phase 1 trial and a second patient enrolled in a compassionate use program reported confirmed partial responses (41 and 60% maximal tumor reduction from baseline) observed after 1.0 and 1.6 years of treatment with AL101, with response durations of 8.6+ and 2.6+ years, respectively 83 .…”
Section: Inhibition Of γ-Secretase In Dtmentioning
confidence: 86%
“…In a phase 1 dose-escalation study of AL101 (NCT01292655 97 ), 94 patients with advanced solid tumors received weekly or bi-weekly intravenous doses of AL101. Of three patients with DT who were enrolled in the study, two experienced confirmed partial responses and one had stable disease as assessed by RECIST v.1.1 criteria 83 , 98 . The maximum tolerated dose was 4 mg QW with no dose-limiting toxicities in seven evaluable patients, and 6 mg Q2W with 1 dose-limiting toxicity in six evaluable patients (grade 3 diarrhea) 98 .…”
Section: Inhibition Of γ-Secretase In Dtmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies have reported tumor regression with two other GSIs: AL101 90 and AL102. 91 Given the promising results obtained to date, several clinical trials of GSIs in DTs are underway (Table 2). 89 A Phase 2 trial (ClinicalTrials.gov identifier NCT04195399) is evaluating nirogacestat in patients aged 1-18 years with DT not amenable to surgery.…”
Section: γ-Secretase Inhibitorsmentioning
confidence: 99%
“…Early studies have reported tumor regression with two other GSIs: AL101 90 and AL102 91 . Given the promising results obtained to date, several clinical trials of GSIs in DTs are underway (Table 2).…”
Section: Systemic Control Strategiesmentioning
confidence: 99%